Preventive effects of crocin on neuronal damages induced by D-galactose through AGEs and oxidative stress in human neuroblastoma cells (SH-SY5Y) - Somaye Heidari; Soghra Mehri; Vahidesadat Shariaty; Hossein Hosseinzadeh (Korean Pharmacopuncture Institute, 2018)
Objective:D-galactose (D-gal) is well-known agent to induce aging process. In the present study, we selected crocin, the main constituent of Crocus sativus L. (saffron), against D-gal- induced cytotoxicity in human neuroblastoma SH-SY5Y cells.Methods:Pretreated cells with crocin (25-500 μM, 24 h) were exposed to D-gal (25-400 mM, 48 h). The MTT assay was used for determination cell viability. Dichlorofluorescin diacetate assay (DCF-DA) and senescence associated β-galactosidase staining assay (SA- β-gal) were used to evaluate the generation of reactive oxygen species and beta-galactosidase as an aging marker, respectively. Also advanced glycation end products (AGEs) expression which is known as the main mechanism of age-related diseases was measured by western blot analysis.Results:The findings of our study showed that treatment of cells with D-gal (25-400 mM) for 48h decreased cell viability concentration dependency. Reactive oxygen species (ROS) levels which are known as main factors in age-related diseases increased from 100 ± 8% in control group to 132 ± 22% in D-gal (200 mM) treated cells for 48h. The cytotoxic effects of D-gal decreased with 24h crocin pretreatment of cells. The cell viability at concentrations of 100 μM, 200 μM and 500 μM increased and ROS production decreased at concentrations of 200 and 500 μM to 111.5 ± 6% and 108 ± 5%, respectively. Also lysosomal biomarker of aging and carboxymethyl lysine (CML) expression as an AGE protein, significantly increased in D-gal 200 mM group after 48h incubation compare to control group. Pretreatment of SHSY-5Y cells with crocin (500 μM) before adding D-gal significantly reduced aging marker and CML formation.Conclusion:Treatment of SH-SY5Y cells with crocin before adding of D-gal restored aging effects of D-gal concentration dependency. These findings indicate that crocin has potent anti- aging effects through inhibition of AGEs and ROS production.